Mitigating Insider Threats in Cybersecurity: A Design Thinking Approach - Anti, Emmanuel; Rousi, Rousi (RWTH Aachen, 2026)
Insider threats in cybersecurity (ITC) are increasing in frequency and impact, while current technical, psychological, and organizational approaches remain insufficient. These strategies often address narrow aspects, such as system vulnerabilities or individual behavior, without offering a holistic, multidisciplinary solution. This study presents DESTIC, a design thinking (DT) framework to study insider threats. Unlike existing research emphasizing only the "Empathize" phase, DESTIC engages all six DT stages: empathize, define, ideate, prototype, test, and implement to uncover root causes and develop targeted interventions. We apply organizational design workshops, a methodology that combines diverse stakeholders to co-create solutions by examining behavioral, technical, and organizational factors. This study offers a structured, human-centered approach to understanding and proactively preventing insider threats through iterative, collaborative cybersecurity innovation.
Keywords: Design thinking; insider threats; human-centered design; cybersecurity; framework; fi=Viestintätieteet|en=Communication Studies|; fi=Viestintätieteet|en=Communication Studies|